Filler flocculation in elastomer blends - an approach based on measured surface tensions and monte carlo simulation. Issue 3 (3rd July 2019) - Gundlach, Norman; Hentschke, Reinhard; Karimi-Varzaneh, Hossein Ali
ABSTRACT: Elastomer materials in car and truck tires require the addition of filler particles for reinforcement and durability as well as the enhancement of other properties of the final product. During the post-mixing stages the previously dispersed filler undergoes (re-)agglomeration in a process called flocculation. The resulting filler network morphology strongly influences the mechanical properties of the rubber material. This means that the structure itself, its dependence on the physicochemical properties of the underlying components, and its attendant influence on, for instance, the dynamic rubber moduli are of significant interest. In this work we discuss a modelling approach to these questions applied to binary blends consisting of natural and styrene-butadiene rubber plus filler of variable type. Our Monte Carlo flocculation simulator utilizes a lattice model of the components, whose thermodynamic development is governed by measured interface or surface tensions. The algorithm minimizes the free enthalpy while the number of MC moves provides a rough measure of time due to the local nature of the moves. We investigate two blend ratios (NR/SBR), i.e., 50/50 and 70/30, as well as two filler volume fractions ϕ, i.e., ϕ = 0.20 and ϕ = 0.25, for variable filler surface tension (both dispersive and polar part, i.e., γ f p and γ f d ). Our results include the scattering momentum transfer characterizing the aggregate size, the fractional interface lengths between the components, and simulated transmission electron micrographs at selected conditions. We discuss how the combination of these quantities can provide information on both the storage and the loss modulus of the materials.